2017
DOI: 10.1163/22105832-00701002
|View full text |Cite
|
Sign up to set email alerts
|

Prehistoric Bantu-Khoisan language contact

Abstract: Click consonants are one of the hallmarks of "Khoisan" languages of southern Africa. They are also found in some Bantu languages, where they are usually assumed to have been copied from Khoisan languages. We review the southern African Bantu languages with clicks and discuss in what way they may have obtained these unusual consonants. We draw on both linguistic data and genetic results to gain insights into the sociocultural processes that may have played a role in the prehistoric contact. Our results show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 40 publications
0
22
0
1
Order By: Relevance
“…During the early phase of contact between agro‐pastoralists and foragers, the survival of the newly arrived food producing societies in an unfamiliar habitat is probably heavily dependent on the knowledge of autochthonous foragers, and as such their contact might be more egalitarian. It has been suggested that Bantu languages of the Kavango‐Zambezi transfrontier region that have incorporated click consonants might have acquired them during this more egalitarian phase, when Khoisan populations had higher social status (Pakendorf, Gunnink, Sands, & Bostoen, ). Later, as Bantu groups became more established and less dependent on local knowledge, they became more socially dominant, and hence sex bias increased in intensity due to the establishment of sociocultural taboos (Destro‐Bisol et al, ).…”
Section: Discussionmentioning
confidence: 91%
“…During the early phase of contact between agro‐pastoralists and foragers, the survival of the newly arrived food producing societies in an unfamiliar habitat is probably heavily dependent on the knowledge of autochthonous foragers, and as such their contact might be more egalitarian. It has been suggested that Bantu languages of the Kavango‐Zambezi transfrontier region that have incorporated click consonants might have acquired them during this more egalitarian phase, when Khoisan populations had higher social status (Pakendorf, Gunnink, Sands, & Bostoen, ). Later, as Bantu groups became more established and less dependent on local knowledge, they became more socially dominant, and hence sex bias increased in intensity due to the establishment of sociocultural taboos (Destro‐Bisol et al, ).…”
Section: Discussionmentioning
confidence: 91%
“…These groups have until recently led a hunter‐gathering way of life; however, other means of subsistence occur as well, for example, the cattle and sheep pastoralism found among the Khoekhoe or the “peripatetic” lifestyle of the Damara . The Khoe‐San have high linguistic, cultural, and genetic diversity, and some groups still preserve their hunter–gatherer lifestyle in remote and isolated areas . Presentations also brought insights into on‐going anthropological and genetic endeavors to encourage investigations of descendants of the earliest southern Africans who are still essentially “forgotten” by the authorities and the scientific community…”
Section: Paleoanthropological and Archaeogenomic Perspectives Of Earlmentioning
confidence: 99%
“…11 The Khoe-San have high linguistic, cultural, and genetic diversity, and some groups still preserve their hunter-gatherer lifestyle in remote and isolated areas. 12,13 Presentations also brought insights into on-going anthropological and genetic endeavors to encourage investigations of descendants of the earliest southern Africans who are still essentially "forgotten" by the authorities and the scientific community. 14 The conference also reexamined ancient urban assemblages and complex spatial and sociopolitical organization at Great Zimbabwe and other Iron Age archeological sites in Africa.…”
Section: Paleoanthropological and Archaeogenomic Perspectives Of Eamentioning
confidence: 99%
“… 15 A piece of evidence for the borrowing of consonantal clicks into Bantu languages is the absence of clicks in Bantu languages outside the area where Khoisan languages are found ( Pakendorf et al, 2017 ). Furthermore, genetic analyses of populations indicate that there was a prehistoric contact between Khoisan and Bantu-speaking populations.…”
mentioning
confidence: 99%
“…For instance, Barbieri et al (2013) undertook an extensive genetic study of the Bantu population in order to elucidate the nature of the borrowing. Their analysis favors “admixture in the maternal line between some of the Bantu groups from Zambia and Khoisan-speaking populations,” suggesting that the borrowing took place through “incorporation of Khoisan women” into the Bantu population; a conclusion endorsed by Pakendorf et al (2017) .…”
mentioning
confidence: 99%